The koala gut microbiome is largely unaffected by host translocation but rather influences host diet - Blyton, Michaela D. J.; Pascoe, Jack; Hynes, Emily; Soo, Rochelle M.; Hugenholtz, Philip; Moore, Ben D. (Frontiers in Microbiology, 2023)
Introduction Translocation is a valuable and increasingly used strategy for the management of both threatened and overabundant wildlife populations. However, in some instances the translocated animals fail to thrive. Differences in diet between the source and destination areas may contribute to poor translocation outcomes, which could conceivably be exacerbated if the animals’ microbiomes are unsuited to the new diet and cannot adapt. Methods In this study we tracked how the faecal microbiome of a specialist Eucalyptus folivore, the koala (Phascolarctos cinereus), changed over the course of a year after translocation. We assessed microbiome composition by 16S rRNA amplicon sequencing of faecal pellets. Results We found no significant overall changes in the faecal microbiomes of koalas post-translocation (n = 17) in terms of microbial richness, diversity or composition when compared to the faecal microbiomes of koalas from an untranslocated control group (n = 12). This was despite the translocated koalas feeding on a greater variety of Eucalyptus species after translocation. Furthermore, while differences between koalas accounted for half of the microbiome variation, estimated diets at the time of sampling only accounted for 5% of the variation in the koala microbiomes between sampling periods. By contrast, we observed that the composition of koala faecal microbiomes at the time of translocation accounted for 37% of between koala variation in post-translocation diet. We also observed that translocated koalas lost body condition during the first month post-translocation and that the composition of the koalas’ initial microbiomes were associated with the magnitude of that change. Discussion These findings suggest that the koala gut microbiome was largely unaffected by dietary change and support previous findings suggesting that the koala gut microbiome influences the tree species chosen for feeding. They further indicate that future research is needed to establish whether the koalas’ gut microbiomes are directly influencing their health and condition or whether aspects of the koala gut microbiomes are an indicator of underlying physiological differences or pathologies. Our study provides insights into how animal microbiomes may not always be affected by the extreme upheaval of translocation and highlights that responses may be host species-specific. We also provide recommendations to improve the success of koala translocations in the future.